Pengaruh Etos Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Produksi Pada PR Alaina Tulungagung - Donny Cantona; Ahmad Jauhari; Lina Saptaria (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the influence of the work ethic and work stress variables on the performance of production employees at PR Alaina Tulungagung. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the saturated sampling method, the number of samples in the research was 60 respondents in production at PR Alaina Tulungagung. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The research results showed that the multiple linear regression equation Y = 10.814 + 0.45X1 + 0.811X2 Work stress has a partially significant effect on employee performance, with a sig. 0.001 > 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that work ethic and work stress have a simultaneous and significant effect on the performance of production employees at PR Alaina Tulungagung.